Tomato activates ethylene signaling to maintain pathogenesis-related genes expression for conferring bacterial wilt resistance - Cai, Weiwei; Li, Qiquan; Liu, Feina; Tao, Yilin; Xu, Zhen; Zhu, Zhujun; Chen, Yuan; Tian, Li (Frontiers in Plant Science, 2026)
Bacterial wilt that caused by Ralstonia solanacearum poses a major threat to tomatoes. Some disease-resistant cultivars have been shown to significantly improve tomato resistance to bacterial wilt. Analyzing and harnessing the resistance mechanism of bacterial wilt-resistant cultivars is therefore of considerable importance for tomato resistance breeding. In this study, we have confirmed that the tomato disease-resistant cultivars “ZJ-7” and “04056” were more resistant to bacterial wilt than the susceptible cultivar Ailsa Craig cv. (AC), and then transcriptome sequencing analysis of roots from “ZJ-7” and “04056” revealed extensive changes in gene expression at 3 and 6 hours post-inoculation (hpi) with R. solanacearum. In both disease-resistant cultivars, the transcriptional expression levels of genes encoding pathogenesis-related (PR) proteins and transcription factors were markedly elevated in response to R. solanacearum infection at both time points. In contrast, the susceptible cultivar AC exhibited a considerably lower number of transcription factors responding to the infection, with up-regulated occuring only at 6 hpi, while the up-regulation of PR gene expression was observed only at 3 hpi. Although the specific up-regulated genes differed between “ZJ-7” and “04056”, both showed activation of ethylene biosynthesis-related genes. Ethephon application in AC promoted the expression of transcription factors at 3 hpi and restore PR gene expression at 6 hpi. These results indicate that sustained defense against bacterial wilt in tomato is closely assocated with ethylene synthesis, providing a theoretical basis for elucidating the resistance mechanism and enhancing disease resistance in tomato.